(untitled) (Fiep Bulletin - online, 2013)
This study aimed to verify lifestyle indicators, such as Physical Activity in Leisure Time, Smoking Habit, Individual Health Perception, Perceived Stress, and Perceived Mood States after Work Hours, of employees of the companies served by SESIGE in Santa Catarina State that were collected in 2011. It also aims to present an overview of the results of these indicators obtained in 2010 and 2011. This survey was carried out in 2012 with the research projects suggested in 2011. Data handling and processing, and statistical analysis were carried out using software Sphinx, version 5.1.0.5. It was used the descriptive analysis considering frequency, percentage and confidence interval of 95.0%, and the chi-square test, adopting the statistical significance level of 99.9% (p? 0,01). Participants of the research totaled 44,857 employees that belong to 266 companies of Santa Catarina State served by SESIGE program, being that 57.2% of the employees are men, the predominant age group is from 18 to 35 years with 68.4% (30,312), and 75.1% (32,891) work in the production sector. It was found that 39.8% (17,688) are physically inactive in leisure time, 40.0% (17,814) have a negative perception of mood states after work, 18.3% (8,135) express a negative perception in relation to stress, 18.9% (8,396) report a negative perception of their own health, 5.8% (2,587) state a negative perception of interpersonal relationships in the workplace, and 9.4% (4,048) smoke. Based on the observed data, it was found that four of the six indicators examined - Physical Inactivity in Leisure Time, Negative Perception of Mood States, Negative Perception of Stress, and Smoking Habit – presented better results in 2011.